Penggunaan Aplikasi Basic Guitar Chords 3D Pada Pembelajaran Seni Budaya (Musik) Di Kelas VII SMP Negeri 3 Kecamatan Harau - Dedi Mantasa; Yos Sudarman (FBS Universitas Negeri Padang, 2020)
This study aims to describe the activities of Culture and Arts (music) teachers in grade VII of SMP Negeri 3 Harau District, Lima Puluh Kota Regency in implementing music instruction using the Basic Guitar Chords 3D application for learning guitar at school. The use of this guitar playing application provides an opportunity for students to learn guitar playing virtually with a different learning atmosphere from how guitar learning was theoretically and practically conducted before. This study uses references to results from relevant research and several theoretical studies especially those related to learning and instruction, learning methods, guitar learning through application, and Culture and Arts (music) instruction in junior high school. This is a qualitative research with a descriptive analysis approach. The object of research was teachers’ activities in implementing music instruction in grade VII of SMP Negeri 3 Harau. The learning observed involves learning guitar under the topic of playing a string instrument in a musical ensemble. The research instruments used were observation notes, interview notes, and document studies. The results of the study explain that learning guitar using the Basic Guitar Chords 3D application can create new experiences for students in learning music using the android application. However, due to the fact that the use of this application coincides with learning musical ensembles under the Basic Competence of playing simple music, this application conceptually does not support learning musical ensembles by using actual musical instruments. However, the teachers’ thought to explain that playing music can be done through application surely gives a point, and it can be developed by the teachers in learning music at school.